A mole of chemistry an historical and conceptual approach to fundamental ideas in chemistry - Desgranges, Caroline; Delhommelle, Jerome (Boca Raton : CRC Press, 2020)
A Mole of Chemistry: An Historical and Conceptual Approach to Fundamental Ideas in Chemistry is intended for students in their undergraduate years who need to learn the basics of chemistry, including science and engineering as well as humanities. This is a companion textbook which provides a unique perspective on how the main scientific concepts describing nature were discovered and, eventually, how modern chemistry was born. The book makes use of context found in history, philosophy and the arts to better understand their developments, and with as few mathematical equations as possible. The focus is then set on scientific reasoning, making this book a great companion and addition to traditional chemistry textbooks. Features: A companion for a general chemistry textbook and provides an historical approach to fundamental chemistry Presents origins of fundamental ideas in chemical science and the focus is then set on scientific reasoning User friendly and with as few mathematical equations as possible About the Authors: Dr. Caroline Desgranges earned a DEA in Physics in 2005 at the University Paul Sabatier - Toulouse III (France) and a PhD in Chemical Engineering at the University of South Carolina (USA) in 2008. Dr. Jerome Delhommelle earned his PhD in Chemistry at the University of Paris XI-Orsay (France) in 2000. He is currently working as an Associate Professor in Chemistry at the University of North Dakota.
OCLC-licensed vendor bibliographic record.
Keywords: Chemistry; Chemistry -- History; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Organic; SCIENCE / Chemistry / Physical & Theoretical